20 is the answer
I hope this help
Answer: - (2 + 3) = -5
<u>Step-by-step explanation:</u>
When combining numbers that have the same sign, you add them and then include the sign.
For example:
-2 - 3 = -(2 + 3) = -5
-6 - 5 = -(6 + 5) = -11
-7 - 8 = -(7 + 8) = -15
Answer:
690 sq in
Step-by-step explanation:
SA = LA + 2B where LA is the lateral area and B is the area of the base
The triangular base has an area of
B = 1/2bh 1/2(5)(12) = 30
LA = ph where p is the perimeter of the base and h is the height of the prism
LA = (12 + 5 + 13)(21) = 30(21) = 630
SA = 630 + 2(30) = 630 + 60 = 690 sq in
Answer:
the answer is s=5/4 minus 1/16
hope this helps :D
Answer:
Step-by-step explanation:
The secants form a proportion where the full length of the secant is the denominator of a fraction where the numerator is the external part of the secant.
7/(x + 7) = 6/(15 + 6) Cross Multiply after combining
7 / (x + 7) = 6/(21)
6 * (x + 7) = 7 * 21 Remove the brackets
6x + 42 = 147 Subtract 42
6x = 147 - 42
6x = 105 Divide by 6
x = 17.5
I think I've done this correctly. If you find an error, please let me know and I'll open it for editing.